MENINGKATKAN MINAT SISWA MELALUI PEMILIHAN MATERI GERAK TARI SMA NEGERI 4 PADANG - Melisa Maya Sari; Yuliasma Yuliasma; Fuji Astuti (FBS Universitas Negeri Padang, 2013)
Abstract Purpose of this research was to reveal the relation of movement selection as intructional materials in accordance with the student’s character with the interest of male students in learning to dance. Data were collected by using qualitative methods, in which the research produced written or oral information from the people, and observing their behavior. Research finding showed that suffle dance moves as material selection which has assertive, strong, and firmly can increase the interest of male students. It can be proved that at the last meeting the students’ want achieved 68.2 %, students’ attention 27.3 % and students’ participation 77.3 %. It can be said that whenever the material selection is in accordance with the learners’ characteristics, therefore, it will give good achievement.